Polyethylene oxide/garnet-type Li6.4La3Zr1.4Nb0.6O12 composite electrolytes with improved electrochemical performance for solid state lithium rechargeable batteries. (3rd May 2019) - He, Kangqiang; Chen, Chenglin; Fan, Rong; Liu, Chen; Liao, Chengzhu; Xu, Yi; Tang, Jiaoning; Li, Robert K.Y.
Abstract: Next generation lithium batteries require new electrolytes with good safety, excellent ionic conductivity, high electrochemical stability and good cycling performance. Herein, we first report a solid composite polymer electrolyte comprises of Li6.4 La3 Zr1.4 Nb0.6 O12 fillers and polyethylene oxide matrix. The ionic conductivity of the solid composite electrolyte is significantly improved to 1.4 × 10 −3  S cm −1 (60 °C) and the electrochemical window is enhanced to 5.2 V, respectively, by incorporation of Li6.4 La3 Zr1.4 Nb0.6 O12 powder at a weight ratio of 0.5:1 with respect to polyethylene oxide. The solid batteries employing the composite electrolytes are able to work at room temperature and have a capacity retention of 99% after cycle. The performance improvement is primarily due to the combined functions of each component in the composite: (i) the incorporation of fillers effectively decreases the crystallinity of PEO, providing more amorphous region for ion conduction; (ii) Li6.4 La3 Zr1.4 Nb0.6 O12 serves as a fast ion conductor in the composite and enhance the electrochemical stability; (iii) the polymer matrix forms intimate surface contact with fillers and electrodes, reducing the bulk and interfacial resistance. The composite polymer electrolyte in this work would be a competitive alternative for the next generation solid state lithium rechargeable batteries.